2006
DOI: 10.1097/01.brs.0000229232.66090.58
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Biomechanics of the Back Muscles in the Lumbar Spine With Reference to Biomechanical Modeling

Abstract: Input parameters, moment arms, as well as physiologic cross-sectional areas have a profound effect on the predicted muscle forces. Therefore, it is important to choose the values for moment arm and physiologic cross-sectional area carefully because they are essential input parameters to biomechanical models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
144
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(154 citation statements)
references
References 99 publications
3
144
0
7
Order By: Relevance
“…Lieber (13) considers that the best information currently available on this issue derives from a study that showed that fast fibers generate just slightly more tension than slow fibers do (80) . As recently reviewed (79) , values for specific tension vary over a large range, between 22.5 N/cm 2 and 100 N/cm 2 . Unfortunately, comparison data for the specific tension of postural HRMT are not available.…”
Section: The Lumbar Multifidus Is the Core Muscle Stabilizer In The Smentioning
confidence: 92%
See 4 more Smart Citations
“…Lieber (13) considers that the best information currently available on this issue derives from a study that showed that fast fibers generate just slightly more tension than slow fibers do (80) . As recently reviewed (79) , values for specific tension vary over a large range, between 22.5 N/cm 2 and 100 N/cm 2 . Unfortunately, comparison data for the specific tension of postural HRMT are not available.…”
Section: The Lumbar Multifidus Is the Core Muscle Stabilizer In The Smentioning
confidence: 92%
“…The lumbar multifidus is the largest and strongest of the low back paravertebral muscles that cross the lumbosacral level, but its exact morphology and role are complex and not fully determined (71)(72)(73)(74)(75) . Nevertheless, rather than its being a prime mover, the specialized multifidus, and especially its deep fibers, are largely credited with postural stabilization of the lumbar spine (40,61,(72)(73)(74)(75)(76)(77)(78)(79) .…”
Section: The Lumbar Multifidus Is the Core Muscle Stabilizer In The Smentioning
confidence: 99%
See 3 more Smart Citations